Improving Survival of Juvenile Scalloped Spiny Lobster (Panulirus homarus) and Crucifix Crab (Charybdis feriatus) Using Shelter and Live Prey - Chia-Huan Ma; Po-Yu Huang; Yung-Cheng Chang; Yen-Ju Pan; Mohamad Nor Azra; Li-Li Chen; Te-Hua Hsu (Animals, 2021)
Cannibalism is a major problem in lobster and crab aquaculture. Reducing the aggressive characteristics of lobsters and crabs can improve survival during the culturing process. In this study, juvenile scalloped spiny lobsters (Panulirus homarus) and crucifix crabs (Charybdis feriatus) were both cultured under different shelter and live prey conditions. Groups with shelter (seaweed and cotton filter) showed a better survival rate than the control group (no shelter; p < 0.05) for both Pa. homarus and Char. feriatus. Co-culturing with live prey (Litopenaeus vannamei) significantly benefited the juveniles of Pa. homarus and visibly increased the survival of juvenile Char. feriatus. Although providing shelter is currently the main method for reducing agonistic behavior, it must be continually altered as the lobsters and crabs grow. Live prey can grow and attract lobsters and crabs to hunt them, and live prey can be supplemented at any time. They can also be used as an additional source of income during the harvest season.